Athlete brand construction: A perspective based on fans' perceptions - Ali Hasaan; Katri Kerem; Rui Biscaia; Kwame J. A. Agyemang
Abstract The purpose of this study was to develop a framework for understanding the antecedents and components of athlete brand. Based on a set of 21 interviews conducted in three different countries, a detailed framework is proposed including five antecedents and two components of athlete brand. The antecedents are media (social media, mass media, video games and major sport events), oral communications (word of mouth, and rumors and narratives), impression management, social agents (parents, family members, friends and community), and teams and sport (sport interest, team interest and team geographical location). In turn, the components of athlete brand are related with on-field attributes (behavior, team, achievements, style of play and skills) and off-field attributes (physical attraction, lifestyle, personal appeal, ethnicity and entertainment). Complementarily, these components of athlete brand are proposed to have an impact on fans' loyalty towards the athlete. Implications of these findings for building and managing athlete brand are discussed, and directions for future studies are provided.